Optimal water tariffs and supply augmentation for cost-of-service regulated water utilities. (June 2015) - Grafton, R. Quentin; Chu, Long; Kompas, Tom
Abstract: We describe how a common method for regulating water utilities, cost-of-service regulation, can both in theory and practice result in the premature and economically inefficient water supply augmentation. Using a dynamic model calibrated to demand and supply conditions in Sydney, Australia we show how to optimally determine the time to supply augment using a 'golden rule' that minimises the average volumetric price paid by consumers. Our results show that, the greater the water scarcity and the longer the operational life of the additional supply, the sooner is the optimal time to augment. Based on our findings, we recommend that price regulators of water utilities adopt an historical cost less depreciation basis for a regulated asset base and a fully flexible and dynamically efficient volumetric pricing that accounts for the marginal opportunity cost of water supplies. Highlights: We show how to determine the optimal time to supply augment using a 'golden rule' that minimises the volumetric price. We find that, the greater the water scarcity and the longer the lifespan of the new supply, the sooner is the augmentation. We recommend that price regulators of water utilities adopt dynamically efficient volumetric pricing.